Green water meal as protein and carotenoid sources in grow-out diets for Pacific white shrimp, Litopenaeus vannamei - Rossita Shapawi,; Najamuddin Abdul Basri,; Sitti Raehanah Muhd Shaleh, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The present study was conducted to evaluate the potential of green water meal (GWM) as an alternative dietary ingredient for juvenile Pacific white shrimp, Litopenaeus vannamei. Five isoproteic and isolipidic diets were formulated with 0% (GWM0, control diet), 10% (GWM10), 20% (GWM20), 30% (GWM30) and 40% (GWM40) of GWM replacing fishmeal protein and fed five times daily to triplicate groups of shrimp with an average initial weight of 6.42±0.02 g. In general, growth performance and feed utilization of shrimp fed with GWM10 did not show any significant differences with the control diet. Survival rate was above 88% and not affected by the dietary treatments. The whole-body protein and lipid of the shrimps decreased with the increasing GWM level in the diets. The shrimps fed with the GWM-based diets (GWM10, GWM20, GWM30 and GWM40) presented more intense red/orange colour and contained higher total carotenoid concentration compare with the control diet. The present findings suggested that GWM is an excellent source of carotenoid for shrimp pigmentation and able to replace fishmeal protein at up to 10% replacement level.